Effective removal of reactive and direct dyes from colored wastewater using low-cost novel bentonite nanocomposites - Chauhdary, Yusra; Hanif, Muhammad Asif; Rashid, Umer; Ahmad Bhatti, Ijaz; Anwar, Hafeez; Jamil, Yasir; A. Alharth, Fahad; Ahmed Kazerooni, Elham (MDPI, 2022)
The present study was aimed to remove direct violet-51, reactive green-5, reactive red, and acid red dyes by novel bentonite clay nanocomposites prepared using sodium metasilicate and potassium ferricyanide. The effect of temperature, pH, adsorbent amount, contact time, and initial concentration were studied to optimize the removal process. Various adsorption isotherms (Temkin, Freundlich isotherm, Langmuir isotherm, Harkin Jura, and Dubinin Radushkevich models) and kinetic models (pseudo-first order and pseudo-second order) were applied to adsorption data to find out the best fit model, i.e., Freundlich isotherm and pseudo-second order model. The prepared samples of bentonite nanocomposites were characterized using scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). Bentonite treated with sodium metasilicate and potassium ferricyanide removed 96.6% of direct violet-51 dye, bentonite treated with sodium metasilicate removed 95%, bentonite treated with potassium ferricyanide removed 94%, and pure bentonite removed 80% of the dye from the solution.